The ambiguities of experience - March, James G. (Messenger lectures., 2010)
Here, March asks a deceptively simple question: What is, or should be, the role of experience in creating intelligence, particularly in organizations? Folk wisdom both trumpets the significance of experience and warns of its inadequacies.